Growth and Biomass Production by Populus deltoides Under Agroforestry in Tarai of Kumaun Region, U.P. - Mohsin, Faiz; Singh, R. P.; Singh, K. (Indian Forester, 1996)
Populus deltoides trees grown in stands treated with various Mint and Cymbopogon spp. attained better height and dbh than their sole stands at their early (2 and 3 years) and advanced (6 and 7 years) ages. The contribution of various components viz., bole branches, foliage and bark to the above ground biomass varied in the sole and treated stands. At all the ages the contribution of bolewood remained highest followed by branches, foliage and bark both in the sole and treated stands. Bolewood contribution was maximum in the sole in comparison to treated stands, whereas contribution of branches, foliage and bark remained highest in the stands treated with M. arvensis and lowest in sole stands. The respective values for other treated stands remained in between the sole and M. arvensis treated stands at all the ages.